Вибір методу і пристрою для визначення діелектричних властивостей молока - Кабалдов, Ю. К.; Лобода, Олександр Іванович; Лобода, Александр Иванович; Loboda, Oleksandr (My University, 2019)
UK: У статті поставлена задача вибрати метод і пристрій для визначення діелектричних властивостей молока. Встановлено, що діелектричні властивості молока можна описати рівнянням комплексної діелектричної проникності. Аналіз рівняння показує, що не зважаючи на вміст в молоці крім жирових включень, також присутні молочній цукор, білки і сухі речовини, саме жири значно впливають на діелектричну проникність. Зміна концентрації жиру у молоці впливає на значення діелектричної проникності по закону близькому до прямолінійного. Точний контроль вмісту жиру в молоці дозволить більш точно визначити режими сушки молока з використанням енергії електромагнітного поля надвисокої частоти. За результатами аналізу останніх досліджень запропоновано і обгрунтовано метод і пристрій для визначення вмісту жиру в молоці за характеристиками електромагнітного високочастотного сигналу, пропущеного через молоко. RU: В статье поставлена задача выбрать метод и устройство для определения диэлектрических свойств молока. Установлено, что диэлектрические свойства молока можно описать уравнением комплексной диэлектрической проницаемости. Анализ уравнения показал, что несмотря на содержание в молоке кроме жировых включений молочного сахара, белков и сухих веществ, именно жировые включения значительно влияют на диэлектрическую проницаемость. Изменение содержания жиров в молоке меняет значение диэлектрической проницаемости по закону близкому к прямолинейному. Точный контроль содержания жира в молоке позволит более точно определить режимы сушки молока с применением энергии электромагнитного поля сверхвысокой частоты. Исходя из результатов последних исследований, предложено и обосновано метод и устройство для определения содержания жира в молоке по характеристикам электромагнитного высокочастотного сигнала, пропущенного через молоко. EN: The article aims to choose a method and device for determining the dielectric properties of milk. For the development of technological processes for the processing of food by the energy of the electromagnetic field of ultra high frequency, as well as devices for the implementation of these processes, information about the dielectric characteristics of the raw material to be processed is required. It is established that the dielectric properties of milk can be described by the equation of complex dielectric permeability. Analysis of the equation showed that, despite the content in milk, in addition to fat inclusions, dairy sugar, proteins and dry substances, it is fat inclusions that significantly affect the dielectric constant. The change in the fat content in milk changes the value of the dielectric constant according to a law close to straight. Accurate control of the fat content in milk will make it possible to more accurately determine the mode of drying of milk using the energy of the electromagnetic field of ultra-high frequency. Offered and proved method and device controls the fat content of milk on the characteristics of high electromagnetic signal passed through the milk. The essence of the method is that milk with different fat content flowing through the covers of the container cell changes the amplitude and phase characteristics of the non-sinusoidal periodic high-frequency electromagnetic signal applied to the covers. Based on the results of recent studies, a method and device for determining the fat content in milk according to the characteristics of an electromagnetic high-frequency signal passed through milk has been proposed and justified.
Выбор метода и устройства для определения диэлектрических свойств молока
Selection method and device for determination of milk dielectric properties
Keywords: діелектричні властивості молока; визначення діелектричних властивостей; діелектрики; вміст жиру в молоці; сушка молока; електромагнітне поле; диэлектрические свойства молока; определение диэлектрических свойств; содержание жира в молоке; сушка молока; электромагнитное поле; dielectric properties of milk; determination of dielectric properties; dielectrics; fat content in milk; drying of milk; electromagnetic field